Abdominal wall reconstruction at the hernioplasty of the big and huge, recurrent median hernias - A A Botezatu (RUDN Journal of Medicine, 2013)
At the solution of problem of hernioplasty of the big and huge postoperative recurrent median hernias alternatively to alloprosthetics were offered various reconstructive autoplastic operations referred on restitution of rectus muscles in natural position with which they occupied before herniation. The series of similar operations is historically surveyed. The preference is given to operation of O. Ramirez which however has number of disadvantages: fragile bracing of medial edges of rectus muscles that leads to frequent recurrences; real danger of occurrence of pararectal hernias. It is shown that the combination of this operation with autodermoplasty promotes substantial improvement of results of treatment. Among 124 operated it is registered 2 (1,6 %) lethal outcomes (in the nearest postoperative period) and 5 (4,0 %) recidives, are taped in the remote terms.